Polysaccharide immunization and colorectal cancer: A systematic review and network meta-analysis - Chen, Yuefeng; Pan, Xinnan; Tian, Baoming; Hu, Yajun (Frontiers in Nutrition, 2022)
Polysaccharides have a variety of biological activities, and in the anti-tumor field, they produce tumor suppressive effects by regulating the polarization of tumor-associated macrophages(TAMs). In immunotherapy, it has significant activities in modulating cytokines and antibody production. We reviewed them and selected CD24, an immune target, for meta-analysis with colorectal cancer (CRC) to investigate the correlation between CD24 expression and CRC.Correlation of CD24 positive expression with clinical-pathological features: age, sex, Duke's stage, diameter, depth of invasion, degree of differentiation, and lymph node metastasis. It showed that: CD24 expression in CRC was significantly correlated with advanced nuclear grade of CRC, lymph node metastasis, Duke's stage of CRC and age of CRC patients, while there was no significant correlation with gender, tumor diameter and invasion depth. The aim is to clarify the specific mechanism of polysaccharide immune anti-tumor, combined with targeted site-specific anti-solid tumor.